(untitled) (International journal of artificial intelligence, 2026)
The article investigates the difficulties and methods of translating flower names through the medium of various cultures and languages. The research scrutinizes the translation process of floral terms between English, Russian, and Uzbek languages, and how the interfacing of botanical naming, cultural meanings, and language rules contributes to it.